Three levels of simple morphophysiological dormancy in seeds of Ilex (Aquifoliaceae) species from Argentina - Galíndez, Guadalupe; Ceccato, Diana Valeria; Bubillo, Rosana Elizabeth; Lindow López, Lucía; Malagrina, Gisela Marina; Ortega Baes, Francisco Pablo; Baskin, Carol C. (Cambridge University Press, 2024)
As a contribution to understanding the world biogeography of seed dormancy in the cosmopolitan genus Ilex, we studied seeds of I. argentina, I. brasiliensis, I. brevicuspis, I. dumosa, I. paraguariensis and I. theezans from the subtropical region of Argentina. We hypothesized that seeds of these species have non-deep simple morphophysiological dormancy (MPD). Effects of temperature, cold stratification and gibberellic acid (GA3) on seed germination and embryo growth were tested. Regardless of incubation temperature, little or no germination occurred for any species until ≥6 weeks. There was an up to 3-fold increase in embryo length to seed length (E:S) ratio before seeds germinated, and embryos grew only during warm-stratifying conditions. Seeds of I. brasiliensis, I. brevicuspis and I. theezans had non-deep simple MPD and germinated to ≥80% after 12, 24 and 16 weeks, respectively. Cold stratification increased germination of I. brasiliensis and I. brevicuspis, and GA3 increased the rate but not final germination percentage of I. brasiliensis and I. theezans. Fresh seeds of I. dumosa required 40 weeks of warm stratification to germinate to 53%, while those after-ripened for 2 months germinated to 81% after 30 weeks; this species has intermediate simple MPD. Seeds of I. argentina and I. paraguariensis germinated to 15 and 21%, respectively, after 40 weeks of warm stratification and did not after-ripen or respond to GA3; these seeds have deep simple MPD. This is the first report of intermediate and deep simple MPD that is broken by warm stratification, thereby increasing our knowledge of seed dormancy in Ilex and in subtropical regions.